Eksplorasi Etnomatematika dalam Permainan Tradisional Egrang di Kudus - Zaky Muflihul Hanan (JUMAT: Jurnal Matematika, 2025)
This research explores the ethnomathematics concepts contained in the traditional game of stilts in Kudus Regency, Central Java. The stilt game was chosen because it contains various mathematical elements that are interesting to explore, such as probability, statistics and trigonometry. This research uses a qualitative approach with ethnographic methods, where data is collected through direct observation, in-depth interviews and document analysis. The research results show that the stilt game contains mathematical concepts that can be used as an effective learning tool for students. By understanding ethnomathematics in stilt games, mathematics can be taught in a way that is more real and related to local culture, thus making mathematics learning more interesting and easier to understand.